Abscisic acid (ABA) inhibits light-induced stomatal opening through calcium- and nitric oxide-mediated signaling pathways - Garcia-Mata, Carlos (2007)
Nitric oxide (NO) is an important signaling component of ABA-induced stomatal closure. However, only fragmentary data are available about NO effect on the inhibition of stomatal opening. Here, we present results supporting that, in Vicia faba guard cells, there is a critical Ca2+-dependent NO increase required for the ABA-mediated inhibition of stomatal opening. Light-induced stomatal opening was inhibited by exogenous NO in V. faba epidermal strips. Furthermore, ABA-mediated inhibition of stomatal opening was blocked by the specific NO scavenger cPTIO, supporting the involvement of endogenous NO in this process. Since the raise in Ca2+ concentration is a pre-requisite in ABA-mediated inhibition of stomatal opening, it was interesting to establish how does Ca2+, NO and ABA interact in the inhibition of light-induced stomatal opening. The permeable Ca2+ specific buffer BAPTA-AM blocked both ABA- and Ca2+- but not NO-mediated inhibition of stomatal opening. The NO synthase (NOS) specific inhibitor l-NAME prevented Ca2+-mediated inhibition of stomatal opening, indicating that a NOS-like activity was required for Ca2+ signaling. Furthermore, experiments using the NO specific fluorescent probe DAF-2DA indicated that Ca2+ induces an increase of endogenous NO. These results indicate that, in addition to the roles in ABA-triggered stomatal closure, both NO and Ca2+ are active components of signaling events acting in ABA inhibition of light-induced stomatal opening. Results also support that Ca2+ induces the NO production through the activation of a NOS-like activity.